Upaya Meningkatkan Efektivitas Informan dalam Mengungkap Peredaran Narkoba oleh Satuan Reserse Narkoba Polres Pasaman Barat: Efforts to Increase the Effectiveness of Informants in Revealing Drug Circulation by the Drug Investigation Unit of the West Pasaman Police - Surya Bakti Siregar (Police Studies Review, 2021)
This research is motivated by the rise of drug trafficking cases in the West Pasaman Regency in recent years. In disclosing the crime of drug trafficking, the role of an informant is needed to find information related to drug trafficking and networks. The existence of this condition affects the disclosure of cases to realize public security and order. The problem in this thesis is the efforts of the drug detective unit in increasing the effectiveness of informants, their use in investigations, and influencing factors. The results of the study which were analyzed using Management Theory, Effectiveness Theory and Cooperation Theory with the concept of Investigation, Informant Concept, and Drug Concept, showed a conclusion that recruiting informants from drug offenders, prisoners, and former drug convicts and former drug addicts by providing rewards with an approach. Supporting factors are the desire for revenge from the informant, personnel capabilities, and planning. The inhibiting factors are the limited budget and lack of community support. Efforts to improve the effectiveness of the informant's performance are increasing supervision and giving rewards and ensuring the confidentiality of the informant's identity. Based on the results of the study, the authors provide suggestions to the Pasaman Barat Police Drug Investigation Unit for investigators to explore the case to find a larger network and ask for backup from the upper unit in terms of personnel limitations, increase the eliciting ability of members to save budget expenditures for informant development, as well as the need for socialization to the public about the protection of identity security for those who provide information related to drug abuse and trafficking, besides that, rewards will also be given in the form of rewards.